Four-Day Workweek as Post COVID-19 Alternate Work Arrangement : The Mediating Role of Organizational Commitment - Roshan, Anannya; Mehta, Prashant (Prabandhan: Indian Journal of Management, 2022)
This study aimed to investigate the post-COVID -19 role of perceived work-life balance and organizational commitment as antecedents to intention to stay in a four-day workweek (FDWW) arrangement. Organizational commitment was hypothesized as a mediator between perceived work-life balance and perceived work engagement. A descriptive approach with a cross-sectional design was adopted for this study. PLS-SEM was used to predict the relationship amongst exogenous and endogenous constructs. Convenience sampling – the snowball method – was used for data collection; owing to COVID-19, this appeared to be the only viable method. The study conceptualized that with pandemic-induced realization about the importance and centrality of familial ties, the employees are likely to have a strong drive towards having a work-life balance. The study, therefore, investigated the significance of a four-day workweek as a post-COVID 19 alternate work arrangement. The findings from the study indicated that with the adoption of a four-day workweek, the organizations could expect greater employee commitment and intention to stay. Another dimension of the study focused on the impact of work engagement on intention to stay, mediated by organizational commitment. The study, based on f2 values, pointed towards a significant role of work engagement in predicting variance in organizational commitment.